Duodenal Dieulafoy lesion: a rare pathogeny of gastrointestinal bleeding in children - Chao, Liu; Lei, Zhang; Xiang, Li (The Turkish Journal of Pediatrics, 2022)
Background. Dieulafoy lesion is a calibre persistent submucosal artery associated with a minuter mucosal defect. Dieulafoy lesion has been reported to account for 1-5.8% of acute nonvariceal upper gastrointestinal bleeding in adults, but it is rarely reported in children. Case. Here we report a case of duodenal Dieulafoy lesion in a 13-year-old boy. After endoscopy and laparotomy, he still had no definite diagnosis and effective treatment. The duodenal Dieulafoy lesion was finally identified by selective angiography and was effectively treated by intravascular embolization. Conclusions. For unexplained upper gastrointestinal bleeding, the possibility of duodenal Dieulafoy lesion should be considered. A combination of multiple diagnosis and treatment methods can improve the success rate of diagnosis and treatment when a single test or treatment method cannot provide definitive diagnosis or effective treatment.